PELATIHAN MASYARAKAT SADAR WISATA DI KECAMATAN KAYANGAN DALAM MENUNJANG PARIWISATA KABUPATEN LOMBOK UTARA - Irwan Suriadi; Himawan Sutanto; Muhammad Mujahid Dakwah (Universitas Mataram, 2022)
Kayangan District, North Lombok Regency is an area with fairly good development in the fields of health infrastructure, education, trade. An issue that is also developing is the immediate construction of a global hub, an international port area that will automatically support tourism. Various cruise ships will come from all over the world so that tourism in the north Lombok district will be more developed. The purpose of this activity is to assist partners in implementing a tourism-aware community in the Kayangan sub-district in welcoming the development of the Kayangan global hub to support the success of tourism in North Lombok (KLU) district. Methods The activities used in achieving the objectives of this activity are to carry out socialization, counseling, training and mentoring. The activities of the PPM Partnership program consist of: (1) socialization, counseling, training and assistance for tourism-aware communities, (2) socialization, counseling, training and marketing assistance for tourism products in North Lombok Regency (KLU). The results of this community service activity are that the community in the Kayangan sub-district in KLU understands the importance of being aware of tourism well by maintaining the cleanliness of the tourist area in Kayangan and in the end it will increase people's income from tourist visits in Kayangan KLU. Conclusion This community service activity is, the Pokdarwis that was formed focused on one village in the Kayangan sub-district, namely in the selengan hamlet whose members consist of youth youth groups, the tourism-aware community in Selegen village, Kayangan sub-district, KLU can also make agro-tourism products, and has produce fishery products for tourists.